Aktivitas Kegiatan Menempel Menggunakan Bahan Alam Untuk Perkembangan Motorik Halus Pada Anak Usia 5-6 Tahun Di Kober Ilham Nioniba - Sere, Asmira; Ngura, Elisabeth Tantiana; Dhiu, Konstantinus Dua; Laksana, Dek Ngurah Laba (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2025)
This study aims to determine the effectiveness of sticking activities using natural materials in supporting the fine motor development of children aged 5–6 years at KOBER Ilham Nioniba. Fine motor skills are an important aspect of early childhood development, especially related to hand-finger coordination. This research uses the Classroom Action Research (PTK) method which is carried out in two cycles.The research subjects consisted of 11 children of group B. Data collection techniques included observation, documentation, and interviews. The results of the study showed a significant improvement in children's fine motor skills after participating in the activity of sticking to natural materials. In the first cycle, the average fine motor ability of the child was 72.8%, increasing to 99.9% in the second cycle. Children show development in the ability to hold, attach, squeeze, and arrange materials with increasingly directed hand-eye coordination. In addition, this activity also increases children's interest and active participation in learning. Thus, the activity of sticking to natural materials has proven to be effective in supporting.